Strategies used in the English translation of Chinese specific terms in government work reports / Tong Xing - Tong, Xing (2016)
Translation is an important aspect in ESL pedagogy among Chinese learners. Translation provides Chinese learners strategies to use in the acquisition of English. By reviewing translated scripts, learners will be able to identify the differences between the Chinese and English language structures. Translating Chinese specific terms in English must be done carefully in order to make sure there is no change in the meaning as well as the purpose of the text. This research aims at investigating the English translation of Chinese specific terms in the 2014 Government Work Report, and to identify the pedagogical implication to Chinese ESL learners. A brief explanation on translation, ESL learning, culture and cultural translation was provided. Definitions and the classification of Chinese specific terms adopted in the report was also provided. A qualitative approach is used to examine the translation of Chinese specific terms using the translation strategies of Venuti (1995),the translation procedures of Newmark (1981, 1988) and the application of Post-colonialism theory in translation. The factors that influenced the choice of translation strategies and procedures on the translated version of the Chinese specific terms were then investigated. The translation of Chinese specific terms must be carefully handled as the process of translation involves cultural transference. This study identified the strategies and procedures involved in ESL pedagogy. From the findings, it was revealed that ESL learners must be flexible in L1 and L2 language transference. The findings of the study that analyzed the translation procedures and translation strategies of the English translated version of the 2014 Chinese Government Work Report. The findings of the study are seen as a learning strategy that can be beneficial for Chinese ESL learners. This research has contributed to the growing literature in the ESL pedagogy framework.